Influence on Individual Finger Stalls in Pain during Acupuncture Operation - TSUNEATSU, Ryutaro; HANDA, Mikako; NAKANO, Hideki; MIYAMOTO, Toshikazu; TOKUTAKE, Tadashi (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 2004)
[Objective] In this study, the pain of receiving acupuncture was evaluated with or without individual finger stalls. [Design] In a randomized, subject- and operating person-blind, controlled study. [Methods] Sixteen acupuncturists and same number of normal volunteers participated in this study. Two needles were inserted into each side of the lumbar muscles. The trials were carried out twice using finger stalls and with bare fingers. These trials were performed in random order. Right after the insertion of needles and at the beginning of electrical stimulation, the subjects were asked to answer a questionnaire about the severity and quality of pain on receiving acupuncture. Durations of procedures were measured. We asked the acupuncturists whether they felt any difficulty in performing acupuncture using finger stalls. [Result] The majority of acupuncturists reported that using the finger stalls during treatment was inconvenient. Although the severity of pain of acupuncture did not significantly differ between that with and that without finger stalls, the average value was slightly higher with finger stalls. The qualities of pain on receiving acupuncture did not significantly differ between the two methods, however, the numbers of selected words differed on some items. The subjects could not recognize the use of individual finger stalls. The use of finger stalls did not influence the duration of the procedure. [Conclusion] In this study, the qualities of pain on receiving acupuncture did not significantly differ between that with and that without finger stalls. The subjects could not recognize the use of individual finger stalls.